2021
DOI: 10.1021/acsnano.1c00380
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Control by Heat Stress Determining Cell Fate to Ferroptosis for Effective Cancer Therapy

Abstract: Flexible manipulation of the fate of cancer cells through exogenous stimulation-induced metabolic reprogramming could handle the cellular plasticity-derived therapies resistance, which provides an effective paradigm for the treatment of refractory and relapsing tumors in clinical settings. Herein, we demonstrated that moderate heat (45 °C) could significantly regress the expression of antioxidants and trigger specific lipid metabolic reprogramming in cancer cells synergized with iron oxide nanoparticles (Fe 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 55 publications
0
75
0
Order By: Relevance
“…A recent study showed that cisplatin loaded iron oxide nanoparticles can induce ferroptosis via accelerated Fenton reaction to inhibit orthotopic brain tumor growth 167 . Iron oxide nanoparticles can also synergize with heat stress to produce overwhelming levels of lipid peroxides, and consequently sensitize the tumor to ferroptosis 168 .…”
Section: Potential Cancer Therapeutic Targets and Biochemical Treatmentsmentioning
confidence: 99%
“…A recent study showed that cisplatin loaded iron oxide nanoparticles can induce ferroptosis via accelerated Fenton reaction to inhibit orthotopic brain tumor growth 167 . Iron oxide nanoparticles can also synergize with heat stress to produce overwhelming levels of lipid peroxides, and consequently sensitize the tumor to ferroptosis 168 .…”
Section: Potential Cancer Therapeutic Targets and Biochemical Treatmentsmentioning
confidence: 99%
“…tPF@PCM mainly accumulated in the liver and spleen, which is in line with other reports of nano-formulations. 45 , 46 Furthermore, there was a moderate aggregation of tPF@PCM at the tumor site, with the highest level observed at 24 h post-injection ( Figure S11 ), which reveals the ideal timing for the initiation of reliable tumor-targeting photothermal therapy.…”
Section: Resultsmentioning
confidence: 98%
“…The heat generated by the MPDA NPs upon NIR laser irradiation boosted the effect of ferroptosis. Furthermore, the application of moderate heat (45°C) in the presence of the IONPs could significantly suppress the expression of the antioxidative proteins and cause tumor cells to undergo specific lipid metabolism ( Xie et al, 2021 ). By virtue of the IONPs and 1H-perfluoropentane (1H-PFP), a heat-responsive ferroptosis strategy was rationally designed by utilizing a polypeptide-modified, IO-containing nanomaterial that loaded 1H-PFP.…”
Section: Nanomaterials As Finsmentioning
confidence: 99%